2005
DOI: 10.1080/13682820400027750
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐visual memory of children with specific language impairment: evidence for generalized processing problems

Abstract: The results indicate that the memory limitations of children with SLI are not restricted to verbal memory, and this fact has implications for its aetiology. Intervention programmes for young children with SLI need to extend beyond language in order to help them develop strategies for processing information in different situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 34 publications
15
104
3
4
Order By: Relevance
“…This finding of no difference on the block span recall task between the children with SLI and their TD peers is in contrast to the finding by Bavin et al (2005) who showed a small but reliable difference between the two groups on a computerized spatial span task. The reason for this difference is not entirely clear but may be because the sample in Bavin et al (2005) was much younger or because they used a computerised task. The finding in the present study may indicate that many children with SLI do not experience domain-general deficits with memory load.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding of no difference on the block span recall task between the children with SLI and their TD peers is in contrast to the finding by Bavin et al (2005) who showed a small but reliable difference between the two groups on a computerized spatial span task. The reason for this difference is not entirely clear but may be because the sample in Bavin et al (2005) was much younger or because they used a computerised task. The finding in the present study may indicate that many children with SLI do not experience domain-general deficits with memory load.…”
Section: Discussioncontrasting
confidence: 99%
“…Children with SLI, who by definition have verbal difficulties, have been reported to show nonverbal difficulties as well (Bavin et al, 2005;Hick et al 2005), particularly in memory span tasks. This study attempted to unpack that finding further by exploring the degree to which the visual and verbal input and response-mode elements of a task might be involved in short term memory performance for all children and whether children with SLI would differ in this regard from their typically developing peers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term memory is known to be deficient in dyslexia (Nicolson & Fawcett, 2000), and it could also play a role in SLI. Computation load has often been singled out as a key problem for children with SLI (Bavin, Wilson, Maruff, & Sleeman, 2005), but whether this problem is specific to language remains to be seen. Problems with sequential material are often mentioned in connection with phonology, but they are also important for syntax and could exist in other dimensions of cognition.…”
Section: Central Processesmentioning
confidence: 99%